2017
DOI: 10.1177/2331216517710354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Energy Equalization on the Intelligibility of Speech in Fluctuating Background Interference for Listeners With Hearing Impairment

Abstract: The masking release (MR; i.e., better speech recognition in fluctuating compared with continuous noise backgrounds) that is evident for listeners with normal hearing (NH) is generally reduced or absent for listeners with sensorineural hearing impairment (HI). In this study, a real-time signal-processing technique was developed to improve MR in listeners with HI and offer insight into the mechanisms influencing the size of MR. This technique compares short-term and long-term estimates of energy, increases the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Although Phatak and Grant (2012) found that linear prescriptive gain cannot restore audibility for low-level consonant information, several researchers have investigated how nonlinear compression schemes can amplify low-level target speech occurring in the dips of a fluctuating masker to improve performance for HI listeners. For example, Desloge et al (2017) andD'Aquila et al (2017) tested an algorithm that selectively amplifies short, low-level portions of a combined speech and noise signal, and found that the algorithm improved performance for maskers containing regular temporal fluctuations. A standard hearing-aid fast-compression algorithm might also improve speech understanding in a fluctuating background (Lunner and Sundewall-Thor en, 2007), especially at low SNRs (Naylor and Johannesson, 2009), although Stone and Moore (2008) cautioned that such an approach could introduce distortion in a speech-on-speech masking situation.…”
Section: G Implications For Hearing-aid Processingmentioning
confidence: 99%
“…Although Phatak and Grant (2012) found that linear prescriptive gain cannot restore audibility for low-level consonant information, several researchers have investigated how nonlinear compression schemes can amplify low-level target speech occurring in the dips of a fluctuating masker to improve performance for HI listeners. For example, Desloge et al (2017) andD'Aquila et al (2017) tested an algorithm that selectively amplifies short, low-level portions of a combined speech and noise signal, and found that the algorithm improved performance for maskers containing regular temporal fluctuations. A standard hearing-aid fast-compression algorithm might also improve speech understanding in a fluctuating background (Lunner and Sundewall-Thor en, 2007), especially at low SNRs (Naylor and Johannesson, 2009), although Stone and Moore (2008) cautioned that such an approach could introduce distortion in a speech-on-speech masking situation.…”
Section: G Implications For Hearing-aid Processingmentioning
confidence: 99%
“…In this case the goal was not to manipulate the existing modulations in speech but to exploit slower fluctuations in signal-to-noise ratio (SNR). By boosting the intensity of low energy portions of the signal, which tend to be speech, they showed improved intelligibility for a group of listeners with hearing loss [see also D'Aquila et al (2017) and Goldsworthy et al (2022) ]. It is worth noting that the non-linear compression that is present in nearly all modern hearing aids acts as an envelope compressor, though compression is typically applied within frequency bands and with a variety of considerations (such as correcting for loudness recruitment) in mind ( Dillon, 2012 ).…”
Section: Introductionmentioning
confidence: 99%